ANALISIS KONSTRUKSI SHARIAH COMPLIANCE PADA PEMBIAYAAN MURABAHAH UNIT JASA KEUANGAN SYARIAH (UJKS) ANNUQAYAH - Holilur Rahman (Fakultas Dakwah Institut Dirosat Islamiyah Al-Amien Prenduan, 2021)
Shariah compliance is an indicator that differentiates Islamic banking from conventional banking. Based on the results of Chapra and Ahmad's research, it proves that shariah compliance has an effect on customer interest. This study uses a qualitative method with a type of field research that uses analytical descriptive. Data collection techniques include observation, interviews, and documentation. The results of the study show that: (1) There are two kinds of indicators of shariah compliance, namely: first, administrative indicators which contain: 1. Contracts, 2. Standard Operating Procedures (SOP), 3. Financial reports, 4. Shariah Opinion, 5. Marketing. Second, the principle indicators which include: 1. Free of Riba, 2. Free of maisir, 3. Free of gharar. (2) the evaluation of the construction of shariah compliance on UJKS Anuqayah murabahah financing generally meets shariah compliance. However, UJKS Anuqayah does not complete the shariah opinion indicator.